Neogene paleoceanography of the eastern equatorial Pacific based on the radiolarian record of IODP drill sites off Costa Rica - Sandoval, María I. (2017)
The Integrated Ocean Drilling Program (IODP) Expedition 344 drilled cores following a transect across the convergent margin off Costa Rica. Two of the five sites (U1381 and U1414) are the subject of the present study. Major radiolarian faunal breaks and characteristic species groups were defined with the aid of cluster analysis, nodal analysis, and discriminant analysis of principal components. A middle-late Miocene to Pleistocene age (radiolarian zones RN5 to RN16) was determined for the sites, which agrees with the nannofossil zonations and 40Ar/39Ar and tephra layers. Considering the northward movement of the Cocos plate (∼7.3 cm/yr), and a paleolatitude calculator, it is assumed that during the Miocene the two sites were located ∼1000 km to the southwest of their current position, slightly south of the equator. The radiolarian faunas retrieved were thus seemingly formed under the influence of different oceanic currents and sources of nutrients. Changes in the radiolarian assemblages at Site U1414 point at dissimilar environmental settings associated with the colder South Equatorial Current and the warmer Equatorial Countercurrent, as well as to coastal upwelling. These differences are best reflected by changes in the abundance of the morphotype Spongurus spp., with noticeably higher values during the Miocene, than in the Pliocene and the Pleistocene. Because Spongurus spp. is generally associated with cooler waters, these abundance variations (as well as those of several other species) suggest that during the Miocene the area had a stronger influence of colder waters than during younger periods. During the Pliocene and the lowermost Pleistocene, biogenic remains are scarce, presumably due to the terrigenous input, which could have diluted and affected the preservation of pelagic fossils, as well as to the displacement of the site to warmer waters. A typically tropical fauna characterized the Pleistocene, yet with widespread presence of colder water species, most probably indicative of the influence of coastal upwelling processes.